Exploring the Role of Propaganda in Shaping National Identity and International Relations: A Comparative Analysis of Azerbaijan, Lithuania, and Turkey in the 21st Century - Binnatli, Azer (Historia i Polityka, 2023)
This study investigates the application of contemporary propaganda theories in analyzing national identity and international relations in the Caspian and Baltic regions during the 21st century. Focusing on the contrasting views of Lippmann, Bernays, and Chomsky, the research explores the relevance of their approaches in the digital age and the role of propaganda in shaping public opinion in Azerbaijan, Lithuania, and Turkey. Employing qualitative methods, the study identifies the significance of Lippmannian and Bernaysian propaganda approaches in these countries, while highlighting the limitations of Chomsky’s perspective in promoting national identity-building and international relations. The research underscores the importance of critical thinking, expert guidance, and understanding the philosophical underpinnings of propaganda theories in navigating complex issues surrounding national identity and international relations. The findings contribute to a deeper understanding of the relationships between media, power, and public opinion, emphasizing the need for a context-specific approach to analyzing the role of propaganda.